A history of modern psychology - Goodwin, C. James; John Wiley & Sons (Hoboken, NJ : Wiley, 2022)
"This chapter opens by describing why it is important to know about history in general and psychology's history in particular. Then a contrast is drawn between traditional histories of psychology, which emphasize the contributions of distinguished psychologists, the outcomes of famous experiments, and the debates among adherents of different "schools" of psychology, and a more recent approach, which tries to situate events and people in a broader historical context. This chapter also considers the methods used by historians to conduct research in history and the problems they face when constructing historical narratives from available data"--
INTRODUCING PSYCHOLOGY'S HISTORY -- THE PHILOSOPHICAL CONTEXT -- THE SCIENTIFIC CONTEXT -- WUNDT AND GERMAN PSYCHOLOGY -- DARWIN'S CENTURY: EVOLUTIONARY THINKING -- AMERICAN PIONEERS -- STRUCTURAL AND FUNCTIONAL PSYCHOLOGIES -- APPLYING THE NEW PSYCHOLOGY -- GESTALT PSYCHOLOGY -- THE ORIGINS OF BEHAVIORISM -- FROM NEOBEHAVIORISM TO COGNITIVE PSYCHOLOGY -- MENTAL ILLNESS AND ITS TREATMENT -- PSYCHOLOGY'S PRACTITIONERS -- PSYCHOLOGY'S ACADEMIC SUBDISCIPLINES -- PSYCHOLOGY IN THE 21ST CENTURY
Includes bibliographical references and index.
Keywords: Psychology -- History -- 20th century; Psychology -- History -- 19th century